2016
DOI: 10.1177/0954407016661440
|View full text |Cite
|
Sign up to set email alerts
|

Potential of variable diffuser vanes for extending the operating range of compressors and for improving the torque performance of turbocharged engines

Abstract: Turbocharging plays a significant role in internal-combustion engines. For engines in the future or for engines operating at a high altitude, compressors which are able to deliver a high pressure ratio are preferable. However, the poor low-end torque characteristics of turbocharged engines, which are often restricted by the narrow operating range of compressors at a high pressure ratio, result in a severe problem for turbocharging. The use of variable diffuser vanes is an effective method to increase the opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…17 and Huang. 18 Since the upstream inlet bend and downstream volute both influence a centrifugal compressor, there would be an interaction between these two components. Zhao.…”
Section: Introductionmentioning
confidence: 99%
“…17 and Huang. 18 Since the upstream inlet bend and downstream volute both influence a centrifugal compressor, there would be an interaction between these two components. Zhao.…”
Section: Introductionmentioning
confidence: 99%
“…They adjusted the radial gap ratio between 1.04 and 1.18 and found that the total pressure ratio of the compressor rises with a decrease of radial gap. In a recent work, Huang et al [15] found that the variable diffuser method can extend the stable operating range of a centrifugal compressor from 23.5% to 54.9% at a pressure ratio of 4.8 with changing the diffuser vane angles by 10 • .…”
Section: Introductionmentioning
confidence: 99%